Developing a biotechnology practicum guidebook for producing nata de coco to increase students’ learning outcomes - Utari, Tri; Lubis, Khairiza; Rahmah, Siti (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to produce a product in the form of a practical work guidebook for making nata de coco to help smooth the practical work process, which was adapted from the development of a 4-D model. The 4-D model consists of 4 stages, namely the stage of defining, designing, developing and disseminating. The level of feasibility of the practical work guidebook is carried out through a validation process by material experts, media experts and supported by responses from teachers and students. The results of the validation carried out by material expert validators and media experts were categorized as